THE EFFECT OF OWN CAPITAL AND TOTAL ASSETS ON REST OF BUSINESS RESULTS (SHU) IN KARTIKA 0302/INHU COOPERATIVE PRIMARY - Gustika, Gita Sari (AGUSPATI Research Institute, 2021)
In running a cooperative business, it is directed to businesses that are directly related to the interests of members, both to support the business and their welfare. The rise and fall of profits (SHU) in savings and loan cooperatives every year is not only influenced by capital factors, but member participation is also one of the important roles in earning profits (SHU), because capital which is the movement of cooperative continuity also comes from members, namely principal savings and mandatory savings. This research was conducted at the Kartika Cooperative Primary 0302/Inhu. The purpose of the study was to determine the effect of Equity Capital and Total Assets on the Remaining Operating Results at the Kartika 0302/Inhu Primary Cooperative, either simultaneously or partially. The method used in this study is a method that uses multiple regression equations. By taking the primary balance sheet document of Kartika Cooperative 0302/Inhu. The analytical technique used in this study is a quantitative technique, namely multiple regression analysis with the help of the SPSS program.The results showed that the Simultaneous Test (F test) obtained the hypothesis that Ho was accepted and Ha was rejected, meaning that Equity Capital and Total Assets simultaneously had no significant effect on the Remaining Operating Results. Partial Test (t test) the effect of Equity Capital on Remaining Operating Results, the hypothesis is that Ho is accepted, Ha is rejected, meaning that Equity partially has no significant effect on the remaining operating results. Partial Test (t test) the effect of Total Assets on Remaining Operating Results, the hypothesis is that Ho is rejected, Ha is accepted, meaning that Total Assets partially has a significant effect on the remaining operating results.